2011
DOI: 10.1590/s1677-04202011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in sensitivity to ambient ultraviolet-B radiation in growth and yield characteristics of eight soybean cultivars grown under field conditions

Abstract: The present study was conducted with eight cultivars of soybean (Glycine max) to determine the effect of exclusion of solar UV-B on the vegetative growth (plant height, leaf area, no. of nodes), UV absorbing compounds (implicated in UV protection) and crop yield (No. of pods and seed weight) and to determine the cultivar difference in their sensitivity to ambient UV-B. Exclusion of solar UV-B enhanced the vegetative growth and yield of all the soybean cultivars. The results showed a significant inverse associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
(26 reference statements)
2
11
0
Order By: Relevance
“…Regarding yield, the present study confirmed a previous report that UV-B causes a reduction in yield potential notably due to smaller number of pods per plant with a reduction of 25% in number of pods per plant with supplemental UV-B over ambient UV-B [15]. Conversely, in a prior study applying the exclusion of UV-B on 8 soybean cultivars, an increase in number of pods per plant of up to 43% was found [2]. In a 2-year study of the effects of UV-B on soybean yield, it was determined that yield reduction was mainly attributable to a change in number of pods per plant under UV-B radiation, which decreased the number of pods per plant of three soybean cultivars by 34.5% on average [19].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding yield, the present study confirmed a previous report that UV-B causes a reduction in yield potential notably due to smaller number of pods per plant with a reduction of 25% in number of pods per plant with supplemental UV-B over ambient UV-B [15]. Conversely, in a prior study applying the exclusion of UV-B on 8 soybean cultivars, an increase in number of pods per plant of up to 43% was found [2]. In a 2-year study of the effects of UV-B on soybean yield, it was determined that yield reduction was mainly attributable to a change in number of pods per plant under UV-B radiation, which decreased the number of pods per plant of three soybean cultivars by 34.5% on average [19].…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies have shown increased number of nodes and pods in eight soybean cultivars after exclusion of UV-B (Baroniya et al 2011). Although UV-B can damage plants, it is proposed to convey photomorphogenic information (Tevini and Teramura 1989).…”
Section: Discussionmentioning
confidence: 99%
“…is one of the most important crops for food, feed, energy production, and industrial resources worldwide. Under supplemental UV-B radiation, soybean cultivars show differences in physiological damage and morphological changes; UV-B-sensitive cultivars show significant yield reductions [6,7,8]. Quantitative trait loci (QTLs) associated with resistance to supplementary UV-B treatment have been identified on chromosomes (Chrs) 3, 6, 7, and 19 using a recombinant inbred line (RIL) population derived from a cross between Keunol (UV-B sensitive) and Iksan10 (UV-B resistant) [9].…”
Section: Introductionmentioning
confidence: 99%